Cerebellar mutism syndrome ater posterior fossa tumor surgery in children: a retrospective single-center study - Schmidt, Stephanie; Kovacs, Edina; Usta, Diren; Behnisch, Rouven; Sahm, Felix; Haux-Nettesheim, Daniel; Witt, Olaf; Milde, Till; Unterberg, Andreas; El Damaty, Ahmed (World neurosurgery, 2023)
Objective - Cerebellar mutism syndrome (CMS) is a well-known complication after posterior fossa tumor surgery in pediatric patients. We evaluated the incidence of CMS in our institute and analyzed its association with multiple risk factors, such as tumor entity, surgical approach, and hydrocephalus. - Methods - All pediatric patients who had undergone intra-axial tumor resection in the posterior fossa between January 2010 and March 2021 were included in the retrospective analysis. Various data points, including demographic, tumor-associated, clinical, radiological, surgery-associated, complications, and follow-up data, were collected and statistically evaluated for an association with CMS. - Results - A total of 63 surgeries in 60 patients were included. The median patient age was 8 years. Pilocytic astrocytoma was the most common tumor type (50%), followed by medulloblastoma (28%) and ependymomas (10%). Complete, subtotal, and partial resection was achieved in 67%, 23%, and 10%, respectively. A telovelar approach had been used the most often (43%) compared with a transvermian approach (8%). Of the 60 children, 10 (17%) had developed CMS and showed marked improvement but with residual deficits. The significant risk factors were a transvermian approach (P = 0.03), vermian splitting when added to another approach (P = 0.002), an initial presentation with acute hydrocephalus (P = 0.02), and hydrocephalus present after tumor surgery (P = 0.004). - Conclusions - Our CMS rate is comparable to those described in the literature. Despite the limitations of the retrospective study design, we found that CMS was not only associated with a transvermian approach but was also associated with a telovelar approach, although to a lesser extent. Acute hydrocephalus at the initial presentation necessitating urgent management was significantly associated with a greater incidence of CMS.